TURISMO RURAL COMUNITARIO UN MEDIO PARA LA ACCIÓN PÚBLICA PARA EL SER HUMANO Y LA VIDA. ESTUDIO DE CASO: PRODUCTO TURÍSTICO RURAL COMUNITARIO, PISTISHÍ - NARIZ DEL DIABLO, EN ECUADOR - Vizuete, Danny Castillo; Flores, Celeste; Zurita, Mónica; Román, Gabriela (European Scientific Journal, ESJ, 2015)
Ecuador is one of twelve mega diverse countries in the world, with a great variety of ecosystems and cultures; it represents eleven percent of the biodiversity on earth. These conditions have allowed the practice of tourist activities in all of its geographical areas. A clear example is Alausí, a town located in the south of the Chimborazo province. Alausí has one of the most outstanding landmarks of Ecuador, known as the “Nariz del Diablo” which is a colossal rock with the shape of a sharp nose, where a railway in zig-zag form runs around it. The name comes from the outstanding difficulties that made it almost impossible for trains to go through the irregular Andean Topography; this route has connected the highlands with the Ecuadorian coast since 1895. In the 1970’s the railway that transported passengers and loads began a downward spiral, therefore in 1990 to 2008 it was abandoned. Soon after the railway was rehabilitated in order to promote tourist activities and boost local economy. However, the rural communities of Pistishi have not benefited, despite of its historical, cultural, scenic value and additionally being the only terrestrial way to visit “Nariz del Diablo”. These facts have encouraged the design and launch of the Rural Communitarian Tourist Product, previously a commercial analysis was executed, and this determined the acceptance and development of sustainable tourist activities for potential tourists. In conclusion, communitarian tourism improves local economy builds a fair society where the center of public action is human life itself and human beings.